Pendidikan Kesehatan Personal Hygiene Saat Menstruasi Pada Remaja Putri Dalam Upaya Peningkatan Kesehatan Reproduksi Di Lingkungan Prate - Ana Lestari; Rafi’ah; Iga Maliga (Yayasan Kajian Riset dan Pengembangan RADISI, 2022)
Personal hygiene health education during menstruation is one of the actions that can be taken to reduce reproductive health problems. Menstrual hygiene and management is an under-recognized problem that has not received adequate attention. This study aims to provide health education on personal hygiene behavior during menstruation in adolescents in the Prate Environment. The indicator of the success of this community service is that young women are able to apply personal hygiene correctly during menstruation to avoid reproductive health problems. The results of service activities for adolescents inform personal hygiene health education during menstruation, adolescents gain new understanding and are able to apply personal hygiene correctly during menstruation.